Hiring Discrimination against Pro-Union Applicants: The Role of Union Density and Firm Size - Stijn Baert; Eddy Omey (Institute for the Study of Labor (IZA), 2014)
We study the causal impact of revealing pro-unionism during the recruitment stage on hiring chances. To this end, we conduct a randomised field experiment in the Belgian labour market. When matched with employer and sector data, the experimentally gathered data enable us to test the heterogeneity of discrimination against pro-union applicants by the union density in the sector and the size of the firm. We find that disclosure of pro-unionism affects hiring chances in a negative way and that in line with our expectations based on the literature this negative impact is stronger in highly unionised sectors.
Keywords: J53; J71; C93; 330; hiring discrimination; union density; trade unions; randomised field experiments